Bioinformatic analysis of post-transmission viral readaptation in Argentine patients with acute HIV-1 infection - Damilano, Gabriel Dario (2020)
During the acute phase of HIV-1 infection, a strong readaptation occurs in the viral population. Our objective was to analyze the post-transmission mutations associated with escape to the cytotoxic immune response and its relationship with the progression of the infection. In this study, a total of 17 patients were enrolled during acute/early primary HIV infection and 8 subjects that were the HIV positive partner resulting in 8 transmission pairs. Genotyping of the genetic polymorphisms of HLA class I A and B was performed using PCR-SSOP. Viral RNA extraction was from plasma. 570 single Gag-gene amplifications were obtained by limiting-dilution RT-PCR. Epitope prediction was performed with NetMHC CBS prediction server for the 19 HLA-A and [sbnd]B alleles. Cytotoxic response prediction was performed by using the IEDB Analysis Resource. From our results, we deduce that the transmitted CTL / gag escape frequency in the founder virus was at least double compared to the post-transmission events. Additionally, by means of an algorithm that combines these frequencies, we observed that the founder viruses better adapted to the HLA A / B alleles of the recipient could contribute to a greater progression of the infection. Our results suggest that there is a large adaptation of HIV-1 to the HLA A / B alleles prevalent in our population. However, despite this adaptive advantage, the virus needs to make “readjustments” through new escape and compensatory mutations. Interestingly, according to our results, this readaptation could have a role in the progression of the infection.